2020
DOI: 10.1161/circinterventions.119.008450
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Long-Term Benefit of Revascularization in Patients With Intermittent Claudication

Abstract: Low risk of procedure-related major amputation following revascularization for intermittent claudication-a population based study Eur J Vasc Endovasc Surg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 84 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…These recommendations are based on data showing that there is a relatively low likelihood of limb loss associated with mild PAD 189 and that long-term improvements in symptomatology may be limited. 190 For example, recent data from the Invasive Revascularization or Not in Intermittent Claudication trial demonstrated that, after 5 years of follow-up, revascularization for claudication lost any early benefit and did not result in long-term health-related quality of life compared with best medical therapy. 190 Despite guidelines recommending medical management as the first-line therapy for claudication, recent registry data from the Vascular Quality Initiative demonstrate that 27% of all open bypass procedures and even a higher percentage of endovascular interventions are performed for claudication.…”
Section: Gaps and Challenges In Revascularizationmentioning
confidence: 99%
See 1 more Smart Citation
“…These recommendations are based on data showing that there is a relatively low likelihood of limb loss associated with mild PAD 189 and that long-term improvements in symptomatology may be limited. 190 For example, recent data from the Invasive Revascularization or Not in Intermittent Claudication trial demonstrated that, after 5 years of follow-up, revascularization for claudication lost any early benefit and did not result in long-term health-related quality of life compared with best medical therapy. 190 Despite guidelines recommending medical management as the first-line therapy for claudication, recent registry data from the Vascular Quality Initiative demonstrate that 27% of all open bypass procedures and even a higher percentage of endovascular interventions are performed for claudication.…”
Section: Gaps and Challenges In Revascularizationmentioning
confidence: 99%
“…190 For example, recent data from the Invasive Revascularization or Not in Intermittent Claudication trial demonstrated that, after 5 years of follow-up, revascularization for claudication lost any early benefit and did not result in long-term health-related quality of life compared with best medical therapy. 190 Despite guidelines recommending medical management as the first-line therapy for claudication, recent registry data from the Vascular Quality Initiative demonstrate that 27% of all open bypass procedures and even a higher percentage of endovascular interventions are performed for claudication. 191 It is possible that many of the patients undergoing revascularization for claudication experienced severe claudication symptoms and that conservative management failed.…”
Section: Gaps and Challenges In Revascularizationmentioning
confidence: 99%
“…Additionally, the IRONIC trial compared revascularization versus SET in addition to optimal medical therapy, and initial follow-up at 1- and 2-years reported improved health-related QOL only in the revascularization group. However, after 5-years of follow-up, the revascularization strategy versus SET plus optimal medical therapy yielded comparable improvements in health-related QOL [141] . In the recent CLEVER trial, SET and endovascular therapy, when combined with optimal medical therapy, were associated with greater improvements in functional outcomes compared with optimal medical therapy alone with no difference in therapeutic efficacy between SET vs. endovascular therapy [142] .…”
Section: Exercise and Peripheral Arterial Disease (Pad)mentioning
confidence: 94%
“…Although endovascular revascularization immediately improves walking ability, supervised exercise requires regular adherence to 3-times-weekly exercise to attain improvement after approximately 6 to 8 weeks of exercise . Patients should be educated about these differences and advised that 25% to 30% of endovascular treatments fail within 5 years and that lower extremity revascularization, but not exercise, is associated with acute limb ischemia . Furthermore, lower extremity revascularization does not reduce rates of coronary events or stroke.…”
Section: Methodsmentioning
confidence: 99%